BEING MUSLIM IN CHINA: HUI ETHNIC PERSPECTIVE - Rosi, Rois Imron (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2020)
Understanding identity helps individual to understand himself/herself and knows his/her position in the society. It is also expected to lead individual having a better tolerant attitude toward other cultures. Furthermore, ‘Hui’ is a Muslim majority ethnic live in China while Muslim as minority group of the country. This study tries to explore Hui ethnic perspective and experience on being Muslim in China. This study is designed qualitatively. The data is presented in the form of description and explanations. The primary research objects are 3 female and 1 male Hui ethnic who are currently living and studying in Indonesia. The result stated that Muslim in China as represented in many Muslim world who are believing in God and practicing rituals, even there are some different practices experienced by Chinese-Muslim. In term of interaction, Chinese-Muslim are more open with other non-Muslim ethnic, and they develop and construct dual identity in order to live in harmony within ‘Han’ majority ethnic group. This study will enrich the sociological analysis of identity within minority group.Keywords: Muslim Identity; Chinese-Muslim; Hui Ethnic